Установившийся спуск авторотирующих аналогов крылаток - Судаков, С.Н. (Механика твердого тела, 2015)
Исследована авторотация свободно падающих в воздухе пластинок, имеющих специальную форму и специальное распределение масс, подобные форме и распределению масс семян клена. Получены уравнения, описывающие установившуюся авторотацию пластинки. С их помощью рассмотрены две задачи. Первая состоит в выяснении вопроса о возможности совершения авторотации пластинкой с заданными массово-геометрическими параметрами. Вторая заключается в нахождении распределения масс, при котором пластинка заданной формы и размеров может совершать установившуюся авторотацию. Autorotations of plates, free falling in air, are investigated in this article. Shape and mass distributions of plates are like ones for seeds of maple. The equations for stationary autorotation revolutions of the plate are obtained. By means of this equations two problems are solved. The first problem is the following. For a plate, the form and distributions of mass of which are given, it is necessary to ascertain the exsistens of stationary autorotation revolutions. And the second problem is the following. For a plate of given form, it is necessary to find out the conditions for distributions of mass, which make possible the exsistens of stationary autorotation revolutions.